Prevention of neurological complications in the surgery of the thoraco-abdominal aorta - Dehtiar, V.; Chanhli, N. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Aortic aneurysm – enlargement of the aorta, caused by pathological changes in the connective tissue structures of its walls [1]. Despite the application of various methods of protection in the surgical treatment of aortic aneurysms, the risk of perioperative complications remains high [4]. The frequency of ischemia of the spinal cord during operations on the thoraco-abdominal aorta reaches up to 13% [3]. The high frequency of spinal complications is explained by the features of the blood supply to the spinal cord (CM), hemodynamic disorders and hemorrhagic complications during surgery [9]. The feasibility of monitoring the pressure and drainage of the cerebrospinal fluid (CSF) is based on the fact that when excessive pressure of the CSB over venous blood pressure is reached, the critical closure pressure, which leads to venous collapse, is achieved. Objective: to present a clinical case of drainage of cerebrospinal fluid during prosthetics of the thoraco-abdominal aorta. Material and methods. The article presents a clinical case of surgical treatment of a patient with aneurysm of the descending section of the thoracic aorta and abdominal aorta, which was performed drainage of the cerebrospinal fluid. Results and discussion. The purpose of setting the spinal catheter is drainage of cerebrospinal fluid for the prevention of ischemic spinal cord and early neurological complications (paraplegia, paraparesis). Increasing the flow to the spinal cord during and after the operation reduces the risk of trembling spinal cord from 2,3–10% to 10–20%. Nevertheless, serious complications, including craniocerebral hematomas, still occur [8]. In general, drainage of cerebrospinal fluid resulted in a 80% reduction in the relative risk of postoperative deficiency. A meta-analysis of 8 studies showed a decrease in postoperative neurological complications in drainage of CSF (p<0.0001) [4]. Conclusions. Patients with intercurrent thoraco-abdominal aorta need to drain the cerebrospinal fluid to prevent early neurological complications (paraparesis, paraplegia).